Infection patterns of scabies and tinea between inland and resettled indigenous Negrito communities in peninsular Malaysia - Er, Yi Xian; Than, Leslie Thian Lung; Muslim, Azdayanti; Yap, Nan Jiun; Tee, Mian Zi; Abdull-Majid, Nurmanisha; Lee, Soo Ching; Shahrizal, Shezryna; Lim, Yvonne Ai Lian (Public Library of Science, 2024)
Skin infections cause significant health burden and affect underserved communities such as the indigenous Negrito communities disproportionately. There is only one study that has addressed skin infections among the Negrito communities, which is the smallest and most isolated indigenous tribe in Peninsular Malaysia, with approximately 6,500 individuals remaining in northern and central Peninsular Malaysia. This study, which aims to update the infection patterns of scabies and tinea among the Negrito communities, recruited 361 participants from eight villages representing all six Negrito subtribes. The results revealed an overall skin infection prevalence of 35.6%, with scabies (11.7%), tinea versicolor (11.3%), and tinea imbricata (7.5%) as major infections, with no co-infection. Notably, infection rates were significantly higher in resettled villages (55.2%) compared to inland villages (24.8%). Scabies and tinea versicolor were more prevalent in resettled villages (21.2% and 23.6%, respectively) than inland villages (6.4% and 4.7%, respectively), while tinea imbricata was more common in inland villages (9.4% vs 3.9%). Furthermore, there exist predisposition of scabies among Kensiu. High prevalence of tinea imbricata was observed among the inland Bateq while prevalence of tinea versicolor was high among the resettled Bateq. Risk analysis revealed specific associations: scabies with Kensiu subtribe (P = 0.002), high income (P = 0.001) and underweight individuals (P = 0.009); tinea versicolor with Bateq subtribe (P = 0.003), resettled villagers (P < 0.001), males (P = 0.040), and overweight/obese individuals (P = 0.015); and tinea imbricata with Bateq (P = 0.011) and smokers (P = 0.004). These findings highlight a complex interplay between environment and lifestyle in skin infection prevalence. Addressing these infections requires targeted interventions, including regular medical care in inland villages and socio-economic support for resettled communities, considering the distinct predispositions in different village types. Copyright: This is an open access article, free of all copyright, and may be freely reproduced, distributed, transmitted, modified, built upon, or otherwise used by anyone for any lawful purpose. The work is made available under the Creative Commons CC0 public domain dedication.